Seismic while drilling imaging in hard rock environment - Sun, Baichun (Curtin University, 2014)
Seismic-While-Drilling is an important technique to obtain updated geological information around borehole. This thesis tackles the challenges of the weak vibration from a diamond drill-bit, and investigates the feasibility of capturing diamond drill-bit signal in hard rock environments. The research includes investigation of the rig noise suppressing, velocity analysis and imaging using the drill-bit signal, and the drill-bit energy radiation. These studies highlighted the importance of future research for applications of SWD in mineral exploration.